Adaptive Gene Content and Allele Distribution Variations in the Wild and Domesticated Populations of Saccharomyces cerevisiae - Han, Da-Yong; Han, Pei-Jie; Rumbold, Karl; Koricha, Anbessa Dabassa; Duan, Shou-Fu; Song, Liang; Shi, Jun-Yan; Li, Kuan; Wang, Qi-Ming; Bai, Feng-Yan (Frontiers in Microbiology, 2021)
Recent studies on population genomics of Saccharomyces cerevisiae have substantially improved our understanding of the genetic diversity and domestication history of the yeast. However, the origin of the domesticated population of S. cerevisiae and the genomic changes responsible for ecological adaption of different populations and lineages remain to be fully revealed. Here we sequenced 64 African strains from various indigenous fermented foods and forests in different African countries and performed a population genomic analysis on them combined with a set of previously sequenced worldwide S. cerevisiae strains representing the maximum genetic diversity of the species documented so far. The result supports the previous observations that the wild and domesticated populations of S. cerevisiae are clearly separated and that the domesticated population diverges into two distinct groups associated with solid- and liquid-state fermentations from a single ancestor. African strains are mostly located in basal lineages of the two domesticated groups, implying a long domestication history of yeast in Africa. We identified genes that mainly or exclusively occur in specific groups or lineages and genes that exhibit evident group or lineage specific allele distribution patterns. Notably, we show that the homing endonuclease VDE is generally absent in the wild but commonly present in the domesticated lineages of S. cerevisiae. The genes with group specific allele distribution patterns are mostly enriched in functionally similar or related fundamental metabolism processes, including the evolutionary conserved TOR signaling pathway.